Using Duolingo in Teaching and Learning Vocabulary: A Systematic Review - Rouabhia, Ridha; Kheder, Khalefa (Indonesian Journal of English Language Studies (IJELS), 2024)
This systematic review examines the extant literature on the efficacy of the Duolingo application for vocabulary development in instructed second language (L2) contexts. Drawing on several empirical studies, the review synthesises findings related to (a) the comparative effectiveness of Duolingo versus traditional pedagogies, (b) the impact of Duolingo on learner motivation and engagement, and (c) practical implications for classroom integration. While the majority of evidence attests to measurable gains in receptive vocabulary knowledge, the findings must be interpreted with caution due to methodological limitations, including small sample sizes, short intervention periods, and construct underrepresentation. The motivational appeal of Duolingo's gamified interface emerges as a prominent theme, corroborated by self-report data. However, the limited research employing psychometrically robust motivational measures precludes definitive conclusions about the temporal stability and transferability of this motivational effect. Theoretically, the provision of individualised feedback aligns with interactionist theories, yet the restricted opportunities for the negotiation of meaning raise doubts about the depth of lexical engagement. Pedagogically, the reviewed studies advocate the careful integration of Duolingo as a supplementary tool within formal instructional contexts. However, optimal implementation strategies remain unspecified, necessitating further classroom-based research employing mixed-methods designs. Significant gaps are identified, including the lack of investigations into the differential impacts of Duolingo's features, vocabulary transfer to authentic communication, and the development of self-regulated learning strategies.